"Since the mine closed down": mining town closures in the songs of Michael Thomas - Genoni, Paul (O L Society Limited, 2002)
This paper considers a group of songs by Australian singer- songwriter Michael (Mick) Thomas that deal with the subject of abandoned mining towns. It considers these songs in the context of a disussion of how personal stories or tales are taken as illustrative of the wider political and social issues arising from the closure or abandonment of such towns.